Strategi Efektif Mengatasi Rasa Malas di Kalangan Mahasiswa untuk Meningkatkan Produktivitas - Gabriel A.P. Saragih; Alan Dwi P Manalu (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
Student productivity is decreasing along with the times, the toughest and biggest challenge for students is laziness. Laziness is a feeling that stems from many things both from the paradigm of thinking and boredom of something that is done continuously. Through this research is to provide effective strategies in overcoming laziness that causes most students to be unproductive. The method used in this research is qualitative method, data collection is done through searching and selecting relevant articles from various scientific sources. The results of the study regarding what strategies are used to overcome laziness to increase student productivity.